Predictive Role of Cyberbullying and Victimization on General Psychological Distress among PhD Students - Vishwakarma, Babita; Kumari, Pushpa; Vishwakarma, Amit Kumar (Indian Journal of Extension Education, 2025)
The study examines the predictive impact of cyberbullying and cyber victimization on general psychological distress (stress, anxiety, and depression) among PhD students. A total of 250 doctoral participants in 2025 (male = 122, female = 128, age mean = 28.02, standard deviation = 2.66) from Banaras Hindu University and Aligarh Muslim University were assessed. A self-prepared demographic survey, Cyber-Bullying and Cyber-Victimization Experience Questionnaire (CBVEQ-E a = .89) and depression, anxiety, and stress scale-21 (DASS-21 a = .89) were used for the purpose. Hierarchical stepwise regression analysis was employed and revealed that cyberbullying significantly positively predicted higher levels of stress (b = 0.236, p < .001), anxiety (b = 0.261, p < .001), depression (b = 0.260, p < .001), explaining 5 to 6.3% of the variance in individual general psychological distress dimensions. Cyberbullying also emerged as a significant predictor of general psychological distress (b = 0.280, p < .001), contributing 7.1% of the variance. These findings underscore the adverse effects of cyberbullying on the mental health of doctoral students due to high-pressure academic environments. The study emphasizes the need for mental health interventions, institutional support systems, and anti-bullying policies to mitigate the negative impact of cyberbullying in academic settings.